MEGAMALL VS MANADO TOWN SQUARE DILEMMA: A COMPARATIVE STUDY ON CONSUMER PREFERENCES FOR SHOPPING DESTINATIONS - ANALYZING MALL ATMOSPHERE AND PRODUCT COMPLETENESS AS KEY FACTORS. - Then, William W.; Saerang, David P. S.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2024)
This research investigates consumer preferences for shopping destinations in Manado, Indonesia, focusing on Mega Mall Manado and Manado Town Square (Mantos), two prominent shopping malls in the region. Through a literature review encompassing consumer behavior and retail management, with an emphasis on store atmosphere, product completeness, and shopping preferences. Quantitative researcher is used for testing objective theories by examining the relationship of variables. The number of samples used in this study is 100 respondents, sampling method that was used is purposive sampling method, with questionnaire as a tool in collecting data. The result shows that There is a differences on Store Atmosphere and Product Completeness of Megamall Manado and Manado Town Square in terms of consumer preferences. Keywords: Celebrity Endorsement, Online Promotion, Online Purchasing Decisions